FGF21 inhibits ferroptosis caused by mitochondrial damage to promote the repair of peripheral nerve injury - Yan, Yao; Ran, Xinyu; Zhou, Zihan; Gu, Yuting; Wang, Rendu; Qiu, Chuanqi; Sun, Yinuo; Wang, Jifeng; Xiao, Jian; Lu, Yingfeng; Wang, Jian (Frontiers in Pharmacology, 2024)
Ferroptosis is a new type of cell death characterized by lipid peroxidation and iron dependency, representing an emerging disease regulation mechanism. The limited understanding of ferroptosis in peripheral nerve injury ( PNI ) complicates the management of such injuries. Mitochondrial dysfunction, a contributor to ferroptosis, further exacerbates the challenges in repairing peripheral nerve damage. This research indicates that PNI causes abnormal accumulation of lipid reactive oxygen species ( ROS ) and inactivation of mitochondrial respiratory chain complex III, leading to mitochondrial dysfunction. This dysfunction, in turn, catalytically oxidizes excessive polyunsaturated fatty acids, resulting in an antioxidant imbalance and loss of ferroptosis suppressor protein 1 (FSP1), which leads to lipid peroxidation. Additionally, irregular iron metabolism, mitochondrial mitophagy, and other factors contribute to the development of ferroptosis. Furthermore, we discovered that FGF21 can mitigate the abnormal accumulation of lipid ROS, restore mitochondrial functionality, and suppress ferroptosis, thereby promoting the repair of PNI. Notably, glutathione peroxidase 4 ( GPX4 ), a target of nuclear factor E2-related factor 2 ( Nrf2 ), and ERK / Nrf2 pathway are involved in the regulation of ferroptosis by FGF21. In summary, controlling ferroptosis is a critical strategy for effective PNI repair.